Relación entre el estado nutricional, calidad de vida y estilo de vida de pacientes en hemodiálisis del Hospital Regional de Loreto, Iquitos 2024 - Quintana Ruiz, Leidy Gabriela (2025)
The present study aimed to analyze the relationship between nutritional status, lifestyle, and quality of life in patients undergoing hemodialysis at the Regional Hospital of Loreto, located in the city of Iquitos, during the year 2024. The study was conducted between May and October and was based on the analysis of nutritional clinical records and the application of the validated KDQOL-36 questionnaire. The initial population consisted of 50 patients; however, the final sample included 29 participants due to deaths, changes in treatment modality, and withdrawal from the hemodialysis program. The results revealed a significant deterioration in nutritional status, as most patients presented a high risk of morbidity and mortality according to body mass index, along with a marked reduction in body reserves and muscle strength. Regarding lifestyle, an overall regular or unhealthy pattern predominated, while the perception of quality of life was mostly unfavorable, particularly in the physical components and the burden associated with kidney disease. Statistical analysis showed significant associations between nutritional status and lifestyle, as well as between nutritional status and quality of life, highlighting the relevance of body composition in overall well-being. In conclusion, patients undergoing hemodialysis at the Regional Hospital of Loreto exhibited persistent nutritional and psychosocial impairment, underscoring the need for a multidisciplinary approach aimed at improving their overall health and quality of life.